The Changing Perspectives of Delinquents and Delinquent Institutions: Theoretical Insights - Bieliūnė, Simona (Acta Paedagogica Vilnensia, 2016)
This article provides theoretical perspectives for analyzing the cause of the behavior that is deemed unacceptable to the public, discusses the changes in the reaction to delinquent behavior in Europe and set models of juvenile justice. Issues related to delinquent behavior, such its stimulating factors, child impunity age, the role of parents and state institutions in the re-socialization process, are analyzed from the historical perspective. While solving children behavior problems, there was always a clash between punishment and education. In this context, the article discusses the key reforms in institutions for delinquent children in Lithuania, the problems of their implementation and changes of their work activities. The author points out that, historically, the role of students in these closed-type schools has changed from passive (obedience and acting according to uniform instructions) to active (acting as equal to others, freely expressing one’s opinion). As a result, it became clear that worldwide trends related to slow practical changes in this closed type of institutions for delinquents are also observed in Lithuania.